Relationship Between Subclinical Hypothyroidism in Pregnancy and Hypertensive Disorder of Pregnancy: A Systematic Review and Meta-Analysis - Han, Yue; Wang, Jun; Wang, Xiaoying; Ouyang, Ling; Li, Yan (Frontiers in Endocrinology, 2022)
Objective: To evaluate the relationship between subclinical hypothyroidism in pregnancy and hypertensive disorders of pregnancy(HDP) to guide clinical practice. Method: We searched the MEDLINE (PubMed), Cochrane Central, EMBASE, Web of Science, and SCOPUS databases and screened all studies evaluating the relationship between subclinical hypothyroidism in pregnancy and hypertensive disorders of pregnancy. Two researchers independently evaluated the quality of all eligible original studies using the Newcastle-Ottawa Scale (NOS). We also performed a meta-analysis using STATA15.1. Sensitivity analyses were also performed by examining the effects of individual studies as well as using different effect models and detecting any publication bias using the harbord test. Results: Twenty-two studies were included in the final meta-analysis. Our results indicated that pregnant women with subclinical hypothyroidism had an increased risk of HDP (OR = 1.54(95% CI: 1.21-1.96) I2=67.1%), compared with euthyroidism. Subclinical hypothyroidism in pregnancy was not associated with hypertensive disorders of pregnancy at TSH diagnostic cut-off of less than 3.0 (P = 0.077). Curiously, the risk of HDP increases when the TSH diagnostic cut-off value is higher or lower than 4 mIU/L. Although only 9 studies were above the threshold, the risk of developing HDP was still 1.69 times, which was highest in all subgroup analyses. This is consistent with the newly recommended diagnostic cut-off value of 4 mIU/L for TSH by the ATA. Our results consider that the risk of hypertensive disorder complicating pregnancy is increased regardless of the diagnosis of subclinical hypothyroidism at any stage of pregnancy. Unfortunately, there is insufficient evidence to support that patients can benefit from treatment with levothyroxine. Conclusion: The results of this meta-analysis indicate that subclinical hypothyroidism in pregnancy is associated with an increased risk of developing HDP, and this association exists regardless of the gestational period. However, the available evidence cannot support these patients receiving thyroxine intervention can benefit from it, so routine screening is only recommended for pregnant women with risk factors for hypothyroidism. Further research is needed to validate more scientific and rigorous clinical studies to clarify the relationship between subclinical hypothyroidism and HDP to improve patient prognosis.